Introduction to blockchain, smart contracts and their relationship with arbitration - Hierro Viétiez, Gonzalo (2021)
Digital transformation is advancing by leaps and bounds. In this scenario, blockchain technology, has successfully positioned itself in the digital and legal world, mainly due to its ability to create an ideal ecosystem for the execution of smart contracts, as well as its usefulness in developing accessible arbitration procedures, especially in small claims disputes.This article provides an overview of blockchain which, although still in its embryonic stage, has demonstrated significant advances in relation to smart contracts and dispute resolution mechanisms. It also outlines the particular qualities of this technology which, when applied in arbitration, represent multiple benefits as opposed to conventional arbitration.